Penggunaan Smartphone pada Konstruksi Belajar Siswa MTs Negeri 7 Model Jakarta - Najwaa Chadeeja Alhady; Ara Fahana Salsabila; Nazula Nur Azizah (Institut Agama Islam Negeri Kendari, 2018)
This paper attempts to determine the characteristics of students in using the internet/smartphone and how the internet/smartphone influence the cognitive, social and emotional development of students. This quantitative research reveals the characteristics of internet usage among teenagers, especially regarding the duration of time to access internet/smartphone, the amount of data usage and source of financing the purchase of data /balance. The results revealed the effect of internet /smartphone on student achievement. Achievements in social, skills and communication subjects have greater scores compared to specific subjects (Mathematics and Science). This explains that students who use the Internet have broader insights, foreign language skills, and are able to develop their creativity. The best time to use is in the range of 7 until 11 hours per week or 1 until 1,5 hours per day. While the use under 7 hours per week and use of over 11 hours per week do not have a significant effect on cognitive improvement